Preparation method of high-strength Al-Cu alloy sheet material reinforced by sinter-free ceramic particles
Patent Information
- Application Number
- CN202611126181.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明要解决的技术问题是:针对现有陶瓷颗粒强化Al-Cu合金制备方法需高温烧结、能耗高、设备要求苛刻且难以兼顾强度与塑性的问题,提供一种工艺简化、能耗低、无需高温烧结,并能相对未强化Al-Cu合金提升屈服强度、且延伸率显著优于原位内生法的Al-Cu合金板材制备方法
[0022](1)免烧结工艺:预制坯体经粉末球磨与冷等静压成型而未经高温烧结,省去了传统陶瓷颗粒强化所需的高温烧结步骤,降低了能耗与设备要求,工艺简化、利于工业化推广;
Smart Images

Figure CN122979690A_ABST
Abstract
Description
Technical Field
[0001] A method for preparing high-strength Al-Cu alloy plates reinforced with ceramic particles without sintering is disclosed, belonging to the field of alloy plate preparation technology. The term "high strength" in this invention refers to the Al-Cu matrix alloy without ceramic particle reinforcement; that is, the yield strength of the embodiments of this invention is higher than that of the unreinforced alloy with the same matrix. Background Technology
[0002] In the process of structural lightweighting in the aerospace and automotive industries, aluminum alloys are widely used due to their low density, high specific strength, and excellent processing and formability. However, traditional aluminum alloys suffer from inherent defects such as insufficient strength at high temperatures, poor creep resistance, and low elastic modulus, which are difficult to completely solve through conventional alloying, plastic deformation, and heat treatment methods, becoming a bottleneck restricting their further development. To improve the comprehensive mechanical properties of aluminum alloys, introducing ceramic particles such as TiC and TiB2 as reinforcing phases, and improving the yield strength and high-temperature performance of the material through particle strengthening mechanisms, is an important research direction in this field.
[0003] In existing technologies, the in-situ endogenous method is one of the mainstream methods for preparing ceramic particle-reinforced aluminum matrix composites. For example, published literature (Heli Peng et al., In-situ tailoring microstructure by directly synthesized TiC-TiB2 nanoparticles to achieve well-balanced strength and ductility in Al-Cu alloy, Materials Science & Engineering A, 2023, Vol. 880) and (Xudong Ma et al., Novel method to achieve synergetic strength-ductility improvement of Al-Cu alloy by in situ TiC-TiB2 particles via direct reaction synthesis, Materials Science & Engineering A, 2023, Vol. 869) both use the method of generating TiC-TiB2 particles in situ within the Al-Cu melt to prepare composite materials. While this method can achieve good interfacial bonding between particles and the matrix, it is complex, costly, and typically involves high-temperature reactions or sintering steps, resulting in high energy consumption, demanding equipment, and low elongation of the obtained material (the measured elongation in the aforementioned literature is only about 5.8%-6.8%), which is not conducive to industrial application. Furthermore, routes such as combustion synthesis also face problems such as uncontrollable side reactions and low production efficiency. Therefore, developing a simplified, low-energy-consumption method for preparing aluminum alloy sheets that does not require high-temperature sintering and can balance strength and ductility is of significant practical engineering importance. Summary of the Invention
[0004] The technical problem to be solved by the present invention is: to address the problems of existing methods for preparing ceramic particle-reinforced Al-Cu alloys, which require high-temperature sintering, have high energy consumption, demanding equipment requirements, and are difficult to balance strength and plasticity, and to provide a method for preparing Al-Cu alloy plates that is simplified, has low energy consumption, does not require high-temperature sintering, can improve the yield strength of Al-Cu alloys compared to unreinforced Al-Cu alloys, and has a significantly better elongation than the in-situ endogenous method.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles includes the following steps:
[0007] Step 1, Preparation of sinter-free TiC / Al and TiB2 / Al ceramic particle preforms: TiC powder and Al powder are mixed at a mass ratio of 1:4 and then ball-milled; TiB2 powder and Al powder are mixed at a mass ratio of 1:4 and then ball-milled. The resulting two mixed powders are then cold isostatically pressed to obtain TiC / Al and TiB2 / Al preforms; the preforms are not sintered at high temperature.
[0008] Step 2, Ceramic particle dispersion and casting in the melt: By mass percentage, an aluminum alloy melt is prepared by dispensing and melting the following components: Cu 4.2-4.8%, Mg 1.5-2.1%, Mn 0.3-0.5%, Ti 0.2-0.4%, B 0.04-0.08%, Zr 0.1-0.3%, unavoidable impurities ≤0.3%, with the balance being Al. The preform is then added to the melt, and the melt is subjected to ultrasonic treatment to disperse the ceramic particles. Subsequently, a Mg agent is introduced, the melt is refined, and the ingot is cast and air-cooled to obtain a micro-nano TiC-TiB2 reinforced Al-Cu alloy ingot.
[0009] Step 3, Preparation of rolled billet: Cut the obtained ingot into squares and remove the surface oxide film;
[0010] Step 4, heat treatment and rolling deformation: The block is subjected to homogenization treatment, rolling deformation, solution treatment and aging treatment in sequence to obtain the high-strength Al-Cu alloy plate reinforced by non-sintering ceramic particles, with an elongation of ≥10%.
[0011] Preferably, in step 1, the TiC powder has a particle size ≤1μm, the TiB2 powder has a particle size ≤1μm, and the Al powder has a particle size ≤5μm. All powders are unoxidized and kept dry. The grinding balls used in the ball mill are ZrO2, the ball-to-material mass ratio is 10:1, the ball milling speed is 100r / min, and the ball milling time is 5-8h. The pressure of the cold isostatic pressing is 300MPa, the holding time is about 5min, and the resulting preform is a φ15mm×70mm column.
[0012] Preferably, in step 2, the raw materials are Al-Cu alloy, pure Mg, Al-Mn alloy, Al-Ti-B alloy, Al-Zr alloy and aluminum ingot, wherein the Al-Cu alloy has an Al-50Cu or lower Cu content, the Al-Mn alloy has an Al-5Mn or lower Mn content, the Al-Ti-B alloy has an Al-5Ti-B content, the Al-Zr alloy has an Al-5Zr or lower Zr content, and the aluminum ingot is high-purity aluminum or 9970 aluminum.
[0013] Preferably, in step 2, the preform is ground into small fragments of about 1 mm before being fed into the melt; the introduced ceramic particles have a content of TiC≤0.45% and TiB2≤0.45% by mass percentage.
[0014] Preferably, in step 2, the parameters for the power ultrasonic treatment are: ultrasonic probe immersion depth in the melt 30mm, ultrasonic power 1200W, and ultrasonic time approximately 2min.
[0015] Preferably, in step 2, the purity of the high-purity argon gas used for refining is ≥99.99%, and the cooling rate of the casting air solidification is controlled at 10-30℃ / s.
[0016] Preferably, in step 2, the metal mold used for casting is made of 45# steel and has dimensions of 130mm×120mm×20mm.
[0017] Preferably, in step 3, the ingot is cut by wire cutting to a thickness of 5-8 cm, and the surface oxide film is removed.
[0018] Preferably, in step 4, the homogenization treatment is carried out in a box furnace or muffle furnace, and after holding at 470°C for 12 hours, it is taken out and air-cooled; the solution treatment is carried out in a tube furnace with high-purity argon gas of 99.99% purity, and after holding at 495°C for 2 hours, it is taken out and quenched in water; the aging treatment is carried out in a box furnace, muffle furnace or oil bath furnace, and after holding at 180°C for 10 hours, it is taken out and air-cooled.
[0019] Preferably, in step 4, the rolling parameters are: roll diameter 150mm, roll temperature 100℃, roll speed 20r / min, and rolling deformation 60%-75%; multi-pass rolling is adopted, with a reduction of 1mm in each pass and a reduction of 0.5-1mm in the last pass, and the sheet is rolled into a 2mm thin plate and then water quenched.
[0020] It should be noted and clarified that the "high strength" referred to in this invention is relative to the Al-Cu matrix alloy without the addition of ceramic particles for reinforcement (i.e., Comparative Example 1 and Comparative Example 2). The yield strength of the embodiments of this invention (391-419 MPa) is higher than that of the unreinforced matrix alloy (363 MPa and 385 MPa). This invention does not compare the absolute strength with the composite materials prepared by the in-situ endogenous method (Comparative Example 3 and Comparative Example 4, yield strength 504 MPa and 529 MPa), but rather anchors the invention on the triple effect of "strength improvement relative to the unreinforced alloy + significantly better elongation than the in-situ method + no sintering and low energy consumption".
[0021] The beneficial effects of this invention are:
[0022] (1) Non-sintering process: The preform is formed by powder ball milling and cold isostatic pressing without high-temperature sintering, which eliminates the high-temperature sintering step required for traditional ceramic particle strengthening, reduces energy consumption and equipment requirements, simplifies the process, and is conducive to industrial promotion.
[0023] (2) Refinement of structure and uniform dispersion of particles: Micro-nano TiC-TiB2 composite ceramic particles serve as heterogeneous nucleation points for the α-Al phase, inducing non-uniform nucleation of α-Al and increasing the nucleation density. On the other hand, they break dendrites and refine grains by means of the acoustic flow and cavitation effect of power ultrasound, and make the ceramic particles uniformly dispersed in the melt. The uniformly dispersed ceramic particles effectively pin the dislocation movement by means of the Orowan bypass mechanism, thereby increasing the yield strength relative to the unstrengthened matrix alloy.
[0024] (3) Synergistic effect of combining strength and plasticity: As shown in Table 1, the elongation of the embodiments of the present invention is 11.2%-16.4% (all ≥10%), which is significantly higher than that of the comparative examples prepared by the in-situ endogenous method (the elongation of comparative examples 3 and 4 is only 6.8% and 5.8% respectively, which is less than half of that of the present invention); at the same time, the yield strength of the embodiments of the present invention is 391-419MPa, which is higher than that of ordinary Al-Cu alloys without the addition of ceramic particles for reinforcement (the yield strength of comparative examples 1 and 2 is 363MPa and 385MPa respectively). While improving the strength of the alloys relative to the unreinforced alloys, the plasticity is significantly better than that of the in-situ method, thus achieving a good balance between strength and plasticity. Attached Figure Description
[0025] Figure 1 The images show BSE (backscattered electron) images of Examples 1-4 (homogenization-rolling-T6 state, T6 state being solution + artificial aging state); a1 and a2 are low-magnification and high-magnification images of Example 1, respectively; b1 and b2 are low-magnification and high-magnification images of Example 2, respectively; c1 and c2 are low-magnification and high-magnification images of Example 1, respectively; and d1 and d2 are low-magnification and high-magnification images of Example 1, respectively.
[0026] Figure 2 The images show the EBSD (Electron Backscatter Diffraction) and recrystallization images of Comparative Example 1 (homogenization-rolling-T6 state);
[0027] Figure 3 The images show the EBSD and recrystallization of Comparative Example 2 (homogenization-rolling-T6 state);
[0028] Figure 4 EBSD and dynamic recrystallization images of Example 1 (homogenized-rolled state);
[0029] Figure 5 EBSD and dynamic recrystallization images of Example 2 (homogenized-rolled state);
[0030] Figure 6 EBSD and dynamic recrystallization images of Example 3 (homogenized-rolled state);
[0031] Figure 7 EBSD and dynamic recrystallization images of Example 4 (homogenized-rolled state);
[0032] Figure 8 The stress-strain curves for the tensile tests of Comparative Examples 1-2 are shown (Comparative Example 1-Base, Comparative Example 2-Base-0.3Ti-0.03B-0.2Zr).
[0033] Figure 9 The engineering stress-strain curves for tensile tests in Examples 1-4 are shown below (Example 1 - Base-0.3Ti-0.03B-0.2Zr-0.3 (TiC-TiB2), Example 2 - Base-0.3T-0.03B-0.2Zr-0.5 (TiC-TiB2), Example 3 - Base-0.3T-0.03B-0.2Zr-0.7 (TiC-TiB2), Example 4 - Base-0.3Ti-0.03B-0.2Zr-0.9 (TiC-TiB2)). Detailed Implementation
[0034] The present invention will be further described below with reference to embodiments and comparative examples, but the scope of protection of the present invention is not limited thereto.
[0035] Comparative Example 1 (without ceramic particle reinforcement)
[0036] This comparative example is an Al-Cu alloy with the following composition by mass percentage: Cu 4.5%, Mg 1.8%, Mn 0.4%, unavoidable impurities ≤0.3%, and the balance being Al.
[0037] Preparation steps: Place Al-50Cu, Al-5Mn, and aluminum ingots into a graphite crucible, heat it in a resistance furnace to 300-400℃ and hold for 20-30 minutes, then heat it to 750-800℃ and hold for about 1 hour to melt it into aluminum liquid, and remove the slag; press pure Mg blocks under the aluminum liquid with a bell jar, stir until melted, hold for 5-20 minutes, and then refine and remove the slag by introducing high-purity Ar (argon gas, purity 99.99%). The ingot was poured into a preheated steel mold (130mm×120mm×20mm) and air-cooled to obtain a casting. It was then wire-cut into 7.5cm thick alloy blocks and the oxide film was removed. The blocks were homogenized at 470℃ for 12 hours and air-cooled. They were then held at 400℃ and rolled in multiple passes to a 2mm thin plate (each pass had a reduction of 1mm, with the final pass being 0.5-1mm), followed by water quenching. The plates were then solution-treated at 495℃ for 2 hours (using 99.99% high-purity argon gas) and water-quenched. Finally, they were aged at 180℃ for 10 hours and air-cooled.
[0038] Comparative Example 2 (Ti, B, and Zr added, but no ceramic particles added)
[0039] This comparative example is an Al-Cu alloy with the following composition by mass percentage: Cu 4.5%, Mg 1.8%, Mn 0.4%, Ti 0.3%, B 0.03%, Zr 0.2%, unavoidable impurities ≤0.3%, and the balance being Al.
[0040] The preparation steps are the same as those in Comparative Example 1, except that Al-5Ti-1B and Al-5Zr master alloys are added to the ingredients.
[0041] Example 1
[0042] This embodiment describes an Al-Cu alloy with the following composition by mass percentage: Cu 4.5%, Mg 1.8%, Mn 0.4%, Ti 0.3%, B 0.03%, Zr 0.2%, TiC 0.15%, TiB2 0.15%, unavoidable impurities ≤0.3%, and the balance being Al. The preparation method includes the following steps:
[0043] Step 1, Preparation of TiC / Al and TiB2 / Al ceramic particle preforms: Weigh TiC powder (approximately 1 μm) and Al powder (approximately 5 μm) at a mass ratio of 1:4 and mix them. Ball mill at 100 r / min for about 6 h. Weigh TiB2 powder (approximately 1 μm) and Al powder in the same way and mix them. Ball mill for about 6 h. The two mixed powders are respectively placed in rubber stoppers, sealed with plastic tape, and vacuum packaged. They are then formed by cold isostatic pressing (pressure 300 MPa, holding pressure for about 5 min). After cleaning, cylindrical preforms are obtained.
[0044] Step 2, Ceramic Particle Dispersion and Casting in the Melt: Al-50Cu, Al-5Mn, Al-5Ti-1B, Al-5Zr, and aluminum ingots are placed in a graphite crucible and held at 300-400℃ for 20-30 minutes, then heated to 750-800℃ and held for about 1 hour to melt and remove slag; the pre-made billet is placed in the melt, and ultrasonic dispersion is performed by immersing an ultrasonic probe to a depth of 30 mm, using a power of 1200W for about 2 minutes; pure Mg blocks are pressed under the aluminum liquid with a bell jar, stirred and melted, and held at the temperature for 5-20 minutes, then refined and removed with high-purity Ar (argon gas, purity 99.99%); the mixture is poured into a preheated steel mold (130mm×120mm×20mm) and air-cooled to obtain micro-nano TiC-TiB2 reinforced Al-Cu alloy ingots.
[0045] Step 3: Cut the ingot into 7.5cm thick alloy blocks using wire cutting and remove the surface oxide film.
[0046] Step 4: Homogenize at 470℃ for 12 hours and air cool; heat at 400℃ for multiple passes to roll into a 2mm thin plate (1mm reduction per pass, 0.5-1mm in the final pass) and then water quench; solution heat at 495℃ for 2 hours (passing 99.99% high-purity argon gas) and then water quench; age at 180℃ for 10 hours and then air cool to obtain the plate of this embodiment (elongation 16.4%).
[0047] Example 2
[0048] The composition is basically the same as in Example 1, except that the total content of introduced TiC and TiB2 is 0.5% (i.e., TiC 0.25% and TiB2 0.25%). The preparation steps are the same as in Example 1 (elongation 14.3%).
[0049] Example 3
[0050] The composition is basically the same as in Example 1, except that the total content of introduced TiC and TiB2 is 0.7% (i.e., TiC 0.35% and TiB2 0.35%). The preparation steps are the same as in Example 1 (elongation 13.3%).
[0051] Example 4
[0052] The composition is basically the same as in Example 1, except that the total content of introduced TiC and TiB2 is 0.9% (i.e., TiC 0.45% and TiB2 0.45%). The preparation steps are the same as in Example 1 (elongation 11.2%).
[0053] Comparative Example 3 (Literature, In-situ Endogenous Method)
[0054] The literature (Heli Peng et al., Materials Science & Engineering A, 2023, Vol. 880) reports that in an Al-5.5Cu-0.45Mn-0.3Ti-0.3V-0.2Cr-0.04B matrix alloy, TiC-TiB2 particles are generated in situ through direct melting reaction of the Al-Ti-B4C-(C / B) system. After solid solution treatment at 538℃ / 10h and aging at 165℃ / 10h (TiC-TiB2 molar ratio 1:2), the yield strength is about 504MPa, the tensile strength is about 553MPa, and the elongation is about 6.8%.
[0055] Comparative Example 4 (Literature, In-situ Endogenous Method)
[0056] The literature (Xudong Ma et al., Materials Science & Engineering A, 2023, Vol. 869) reports that TiC-TiB2 particles are synthesized in situ through direct reaction in an Al-5.5Cu-0.45Mn-0.3Ti-0.3V-0.2Cr-0.14Zr-0.04B matrix alloy. After solution treatment at 538℃ / 10h and aging at 165℃ / 10h, the yield strength is about 529MPa, the tensile strength is about 584MPa, and the elongation is about 5.8%.
[0057] Comparative Example 5 (Literature, In-situ Endogenous Method)
[0058] The literature (Yuyang Gao et al., Materials Science & Engineering A, 2019, Vol. 764) reports that after introducing biphasic submicron / nano TiB2-TiC particles into an Al-5.0Cu-0.6Mg-0.5Si matrix alloy, and then hot-extending at 500℃, followed by solution treatment at 505℃ for 2 hours and aging at 160℃ for 18 hours, the yield strength is about 348 MPa, the tensile strength is about 517 MPa, and the elongation is about 14.5%.
[0059] Table 1. Test results of mechanical properties of each sample
[0060] sample Yield strength (MPa) Tensile strength (MPa) Fracture strain (%) Comparative Example 1 363 477 12.3 Comparative Example 2 385 504 19.4 Comparative Example 3 504 553 6.8 Comparative Example 4 529 584 5.8 Comparative Example 5 348 517 14.5 Example 1 391 509 16.4 Example 2 402 527 14.3 Example 3 405 532 13.3 Example 4 419 530 11.2
[0061] As shown in Table 1, under the non-sintering and low-energy consumption process, the yield strength (391-419 MPa) of the embodiments of the present invention is higher than that of the unstrengthened Al-Cu alloy (Comparative Example 1 and Comparative Example 2), and the elongation (11.2%-16.4%, all ≥10%) is significantly higher than that of the in-situ endogenous method (Comparative Example 3 and Comparative Example 4, only 5.8%-6.8%). This achieves a good balance between the relative strength improvement of the unstrengthened alloy and the significantly better elongation than the in-situ method. At the same time, the embodiments of the present invention eliminate the high-temperature sintering step, which significantly reduces the process energy consumption and equipment requirements.
[0062] Verification Statement: The mechanical property data of Examples 1-4 in Table 1 above are all measured values under specified process conditions of the specific embodiments of the present invention; Comparative Examples 1 and 2 are measured values under the same conditions; Comparative Examples 3, 4, and 5 are values disclosed in the corresponding literature. The technical effect of the present invention is based on the measured data, and each comparative example is only used to illustrate the relative differences in technical effects. All data are recorded in the literature and directly cited.
Claims
1. A method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles, characterized in that, Includes the following steps: Step 1, Preparation of sinter-free TiC / Al and TiB2 / Al ceramic particle preforms: TiC powder and Al powder are mixed at a mass ratio of 1:4 and then ball-milled; TiB2 powder and Al powder are mixed at a mass ratio of 1:4 and then ball-milled. The resulting two mixed powders are then cold isostatically pressed to obtain TiC / Al and TiB2 / Al preforms; the preforms are not sintered at high temperature. Step 2, Ceramic particle dispersion and casting in the melt: By mass percentage, an aluminum alloy melt is prepared by dispensing and melting the following components: Cu 4.2-4.8%, Mg 1.5-2.1%, Mn 0.3-0.5%, Ti 0.2-0.4%, B 0.04-0.08%, Zr 0.1-0.3%, and unavoidable impurities ≤0.3%, with the balance being Al. The preform is then added to the melt, and the melt is ultrasonically treated to disperse the ceramic particles. Subsequently, a Mg agent is introduced, the melt is refined, and the melt is cast and air-cooled to obtain a micro-nano TiC-TiB2 reinforced Al-Cu alloy ingot. Step 3, Preparation of rolled billet: Cut the obtained ingot into squares and remove the surface oxide film; Step 4, heat treatment and rolling deformation: The block is subjected to homogenization treatment, rolling deformation, solution treatment and aging treatment in sequence to obtain the high-strength Al-Cu alloy plate reinforced by non-sintering ceramic particles, with an elongation of ≥10%.
2. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 1, the TiC powder has a particle size ≤1μm, the TiB2 powder has a particle size ≤1μm, and the Al powder has a particle size ≤5μm. All powders are unoxidized and kept dry. The grinding balls used for ball milling are ZrO2, the ball-to-material mass ratio is 10:1, the ball milling speed is 100r / min, and the ball milling time is 5-8h. The pressure of the cold isostatic pressing is 300MPa, the holding time is about 5min, and the resulting preform is a φ15mm×70mm column.
3. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 2, the raw materials are Al-Cu alloy, pure Mg, Al-Mn alloy, Al-Ti-B alloy, Al-Zr alloy and aluminum ingot. The Al-Cu alloy has an Al-50Cu or lower Cu content, the Al-Mn alloy has an Al-5Mn or lower Mn content, the Al-Ti-B alloy has an Al-5Ti-B content, the Al-Zr alloy has an Al-5Zr or lower Zr content, and the aluminum ingot is high-purity aluminum or 9970 aluminum.
4. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 2, the preform is ground into small pieces of 1 mm before being fed into the melt; the introduced ceramic particles have a content of TiC≤0.45% and TiB2≤0.45% by mass percentage.
5. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 2, the parameters for the ultrasonic treatment are: ultrasonic probe immersion depth in the melt 30mm, ultrasonic power 1200W, and ultrasonic time 2min.
6. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 2, the purity of the high-purity argon gas used for refining is ≥99.99%, and the cooling rate of the casting air solidification is controlled at 10-30℃ / s.
7. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 2, the metal mold used for casting is made of 45# steel and has dimensions of 130mm×120mm×20mm.
8. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 3, the ingot is cut by wire cutting to a thickness of 5-8cm, and the surface oxide film is removed.
9. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 4, the homogenization treatment is carried out in a box furnace or muffle furnace, held at 470℃ for 12 hours, and then removed and air-cooled; the solution treatment is carried out in a tube furnace with 99.99% high-purity argon gas introduced, held at 495℃ for 2 hours, and then removed and quenched in water; the aging treatment is carried out in a box furnace, muffle furnace or oil bath furnace, held at 180℃ for 10 hours, and then removed and air-cooled.
10. The method for preparing high-strength Al-Cu alloy plates reinforced with non-sintering ceramic particles according to claim 1, characterized in that, In step 4, the rolling parameters are: roll diameter 150mm, roll temperature 100℃, roll speed 20r / min, and rolling deformation 60%-75%; multi-pass rolling is adopted, with a reduction of 1mm in each pass and a reduction of 0.5-1mm in the last pass, and the sheet is water-quenched after being rolled into a 2mm thin plate.